Islamization of Melayu-Nusantara Society through Language Approach according to Syed Muhammad Naquib Al-Attas - Enri Auni, Azrul Kiromil; Hermanto, Hermanto (Khalifa Journal of Islamic Education, 2020)
One of the approaches used as an instrument of dakwah as well as islamization in Malay-Nusantara community is language approach. In general, islamization using language approach was carried out in two types, namely by adopting the Arabic words into Malay (lafzhi) and by maintaining the native words of Malay patterned with Hindu-Buddhist nuances but having meaningful Islamic values (maknawi). The objective of this research is to analyze islamization of Malay-Nusantara community through the language approach according to Syed Muhammad Naquib Al-Attas. This research used qualitative method with an individual life history approach. All sorts of data were collected from the biographical books of Syed Muhammad Naquib Al-Attas, literature study, documentaries, and various written and physical works of Syed Muhammad Naquib Al-Attas. The process of data collection was done by collecting, reducing, presenting, and formulating conclusion.The results show that islamization by language approach, both lafzhi and maknawi, had a significant influence on islamic society of Malay-Nusantara, especially in Indonesia. It is proven by the establishment of formal Indonesia language that used Arabic and Malay words and patterns and adopted some of those words in the five principles of Pancasila.